Eficiência agronômica de fertilizantes organominerais nitrogenados a base de biocarvão em arroz de terras altas - Santos, Bruna Larissa da Silva dos (2021)
Biochar-based organomineral fertilizers can contribute to increased nitrogen use efficiency, mainly due to the slow release of nutrients, as well as their potential to reduce losses through volatilization and leaching. The objective of this study was to develop and evaluate the agronomic efficiency of nitrogen organomineral fertilizer formulations based on biochar. For this, two experiments were carried out, one in clayey soil and the other in sandy texture soil, in a 5x4 factorial scheme for each soil, in a greenhouse at Embrapa Agrossilvipastoril in Sinop-MT, using the grow crop of highland rice (Oryza sativa L.) BRS Esmeralda. The treatments consisted of the application of urea mineral fertilizer and organomineral fertilizers obtained from the mixture and pelleting of biochar and urea in proportions 2:1 (FOM2:1), 1:2 (FOM1:2) and 1:4 (FOM1 :4) and five doses of nitrogen (0, 75, 150, 300 and 600 mg dm-3 ). The experimental design used was in completely randomized blocks, with four replications. The SPAD index (CLORTOT), tiller number (PERF), panicle number (PAN), shoot dry mass (MSPA), and grain dry mass (MSG) were determined. The Agronomic Efficiency Index (IEA%) of fertilizers was also calculated. For CHLORTOT there was a linear effect regarding N doses (p < 0.0001). For PERF, there was a difference between the doses, where the quadratic polynomial regression was significant. There was a difference between the urea sources and the FOM's at the highest dose of N applied to PAN, with a quadratic effect for both, with maximum estimated values of 7.7 panicles per plant for urea at a dose of 358 mg dm-3 , and 8.1 panicles with organomineral fertilization at a dose of 469 mg dm-3 . MSPA production in clayey soil responded only to N rates, with maximum production of 44 grams per pot at a rate of 527 mg dm-3 . In sandy soil, there was a significant interaction between fertilizers and doses (p = 0.0485), with lower MSPA production at the highest dose of N via urea. For MSG in sandy soil the grain yield obtained with urea and FOM1:4 was lower than the other FOM's at the highest dose evaluated. In the clayey soil, there were also no differences between the sources, with a maximum production of 47 grams per pot at a dose of 594 mg dm-3 of N. The formulations of organomineral fertilizers were more efficient than urea in sandy soil, with emphasis on the formulation with the highest proportion of biochar (2:1).